Sintering Characteristics of Ceramsite Manufactured from Blast Furnace Slag and Sewage Sludge - Wang, Z.L. (Asian Journal of Chemistry, 2013)
To develop the recycling of solid wastes, blast furnace slag (BFS) and sewage sludge (SS) were added as components for making ceramsite. This study examined the sintering characteristics of ceramsite at different sintering temperatures and duration and different mass ratios (BFS: SS: clay). The results show that as the sintering temperature and duration increased, the pore size diameter gradually increased up to the maximum of 120 nm at 1100 ºC, 20 min. The turn point of the pore size diameter was at 1050 ºC, 20 min. Corresponding to the variation of the pore size diameter, the highest and lowest porosity of ceramsite reached 88 % and 62 %, respectively. The different mass ratios of three raw materials (BFS, SS and clay) had no obvious effect on the thermal behaviours of ceramsite and mostly the same trends of variation appeared in the curves of DT-TG. With the sintering temperature increasing, the complex crystalline phases appeared at 900 ºC and no variation happened on the main crystalline phases except the transformation from akermanite (Ca2MgSi2O7) to gehlenite [Ca2Al(AlSiO7)] at 1050 ºC.